Meta-analysis of the Effects of Salinity Stress on Cotton (Gossypium spp.) Growth and Yield in Iran - Azadeh Razaji; Farzad Paknejad; Mohammad Nabi Ilkaee; Maryam Moarefi; Abdolmajid Mahdavi Damghani (Journal of Agricultural Sciences)
Research on the impact of inputs has a long history in the country; however, because of the dispersion and diversity in the results of various experiments, it is difficult to achieve a general conclusion. In this study, a meta-analysis approach has been used to overcome this problem in order to achieve a single result by integrating and re-analyzing the findings of independent experiments. For this purpose, scientific articles published by researchers of the country regarding the effect of salinity stress on cotton yield were investigated. Articles were selected so that, in their meta-analysis of data required to perform there. The data necessary for the implementation of the meta-analysis is present in them. The results of this study showed that from 1996 to 2017; 15 papers and thesis were published on the effects of salinity stress on yield, early maturing and number of bolls in upland cotton (Gossypiumhirsutum L.). With increasing salinity stress, yield and number of bolls decreased. The standardized values for salinity stress effect on cotton yield were significant in all five treatments (control via salinity, control via 2-3 dS m-1, control via 4-5 dS m-1, control via 6-7 dS m-1, control via 8-9 dS m-1) compared to control (P<0.001). The standardized values of the effect of salt stress on cotton aging were significant in all five treatments compared to control. The standardized values of the effect of salt stress on cotton aging were significant in all five treatments compared to control. Results showed increasing salinity stress can cause early maturing in cotton. The standardized values for the effect of salinity stress on number of bolls per cotton plant, in the comparison of the total treatments of salinity stress, 2-3 dS m-1, 6-7 dS m-1 and 8-9 dS m-1 were significant compared tocontrol (P<0.001). In general, the results of this study showedthat salinity stress can reduce yield of cotton by reducing thenumber of bolls and also can cause early maturing on cotton.